Leishmania Spp-Host Interaction: There Is Always an Onset, but Is There an End? - Conceição-Silva, Fatima; Morgado, Fernanda N. (Frontiers in Cellular and Infection Microbiology, 2019)
For a long time Leishmaniasis has been considered as a priority in public health all over the world for different aspects such as geographic spread, number of population living at risk of infection as well as the potential lethality and/or the development of disfiguring lesions in the respectively visceral and tegumentary forms of the disease. As a result, several groups have been bending over this issue and many valuable data have been published. Nevertheless, parasite-host interactions are still not fully known and, consequently, we do not entirely understand the infection dynamics and parasite persistence. This knowledge may point targets for modulation or blockage, being very useful in the development of measures to interfere in the course of infection/ disease and to minimize the risks and morbidity. In the present review we will discuss some aspects of the Leishmania spp – mammalian host interaction in the onset of infection and after the clinical cure of the lesions. We will also examine the information already available concerning the parasite strategy to evade immune response mainly at the beginning of the infection, as well as during the parasite persistence. This knowledge can improve the conditions of treatment, follow-up and cure control of patients, minimizing the potential damages this protozoosis can cause to infected individuals.